Asociación entre el arbusto Capparis retusa (Capparidaceae) y las hormigas Camponotus blandus y Acromyrmex striatus (Hymenoptera: Fo - Farji Brener, Alejandro G (Universidad de Costa Rica, 1992)
The hypothesis that the nectivore ant Campollotus blandus operates as an altemative defense of the shrub Capparis retusa against the leaf-cutting ant Acromyrmex striatus was tested. Data were obtained in a fores! reserve of the Argentinean subtropical dry Chaco (250 55' S, 62005' W) during the spring of 1986. C. refusa is abundant, but it is nol a pan of the leaf-cutting ant diet « 1 %), has a high proportion of nectivore ant visits. and low levels of chemical and physicaldefenses. Shrubs wit hout C. blalldus were intensively harvested by A. striatus, whích suggests that the nectivore ant is an altemative defense for the shrub against the leaf-ccutting ant.